An Analysis of Fiqh Learning Materials On The Validity Of A Fasiq Guardian In Marriage: Perspectives From The Four Sunni Madhhabs And The Compilation Of Islamic Law - Zaenal Abidin; Muhammad Syakur; Joni; Hamidulloh Ibda; Sumarjoko; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This study examines the learning materials of the four major schools of Islamic jurisprudence (Hanafi, Maliki, Shafiʿi, and Hanbali) in comparison with the Compilation of Islamic Law (KHI) in Indonesia regarding the validity of a fāsiq guardian (wali fāsiq) in marriage. The issue of guardianship in marriage holds a central position within Islamic family law because the presence of a guardian (wali) constitutes one of the legal pillars (arkān) of marriage. The problem arises when the appointed guardian is in a state of fisq—known for committing major sins, persistently engaging in disobedience, or lacking moral integrity. This condition creates a juridical and theological debate among classical jurists concerning whether such a guardian retains legal authority or is disqualified. Using a normative-juridical and comparative approach, this research analyzes primary classical sources of fiqh, modern scholarly contributions, and statutory frameworks. Data were collected through a library study of authoritative fiqh texts, scholarly journals, and the Compilation of Islamic Law. The study finds that the Hanafi school tends to permit the wali fāsiq to exercise guardianship, emphasizing the preservation of marriage validity. Conversely, the Maliki, Shafiʿi, and Hanbali schools generally reject the authority of a fāsiq guardian, grounding their argument on moral integrity (ʿadālah) as a prerequisite for guardianship. The KHI aligns more closely with the Shafiʿi perspective, emphasizing the moral qualifications of the guardian to ensure justice, harmony, and protection of women’s rights in marriage contracts. The findings highlight the significance of integrating classical jurisprudence with the socio-legal context of Indonesia. By aligning statutory regulations with ethical principles derived from the Shafiʿi tradition, the KHI strengthens legal certainty and moral accountability in family law. This research contributes both theoretically and practically to the development of Islamic family law in Indonesia, offering insights for judges, legal practitioners, and Islamic scholars in addressing contemporary marital issues.